On the potential biological impact of radiation-induced acoustic emissions during ultra-high dose rate electron radiotherapy: a preliminary study. (7th March 2023) - Lascaud, Julie; Parodi, Katia
Abstract: Ionizing radiation pulses delivered at ultra-high dose rates in emerging FLASH radiotherapy can result in high-intensity low-frequency thermoacoustic emissions that may have a biological impact. This study aims at providing insights into the thermoacoustic emissions expected during FLASH radiotherapy and their likelihood of inducing acoustic cavitation. The characteristics of acoustic waves induced by the energy deposition of a pulsed electron beam similar to previous pre-clinical FLASH radiotherapy studies and their propagation in murine head-like phantoms are investigated in-silico. The results show that the generated pressures are sufficient to produce acoustic cavitation due to resonance in the irradiated object. It suggests that thermoacoustics may, in some irradiation scenarios, contribute to the widely misunderstood FLASH effect or cause adverse effects if not taken into account at the treatment planning stage.